Carbon dioxide measurements using long period grating optical fibre sensor coated with metal organic framework HKUST-1 - Hromadka, Jiri; Tokay, Begum; Correia, Ricardo; Morgan, Stephen P.; Korposh, Sergiy (Elsevier, 2018)
An optical fibre long period grating (LPG) based carbon dioxide (CO2) sensor coated with HKUST-1, a material from the metal organic framework family, functional coating is presented. In-situ crystallization and layer by layer (LbL) techniques of HKUST-1 thin film synthesis are compared in terms of the feasibility of the deposition procedure (time and cost efficiency) and the sensitivity of the film to carbon dioxide. The sensing mechanism is based on the measurement of the change of the refractive index (RI) of the coating that is induced by the penetration of CO2 molecules into the HKUST-1 pores. The HKUST-1 film was characterized by scanning electron microscopy (SEM). The thickness and refractive index (RI) of the 10, 20 and 40 layers thick films were determined using ellipsoetry. The crystallinity of the films was examined by X-ray diffraction pattern (XRD). While no response to CO2 was observed for the sensor coated using the in-situ crystallization technique, an LPG modified with 10, 20 and 40 layers of HKUST-1 films using LbL method upon exposure to CO2 in the range of 500 ppm to 40,000 ppm showed good sensitivity. The film containing 40 layers exhibited the highest sensitivity to CO2 with an obtained detection limit of 401 ppm.